PENGEMBANGAN MEDIA PENGGARIS KONVERSI KILAN UNTUK MEMFASILITASI KEMAMPUAN PENGUKURAN DAN MENGESTIMASI PANJANG PADA SISWA KELAS 2 SEKOLAH DASAR - Silmadina Azkiya; Mira Azizah; Bagus Ardi Saputro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Based on the results of interviews and observations with class 2 teachers, it can be seen that teachers only use guidebooks such as textbooks and worksheets as learning resources when learning takes place. The teacher has media related to measuring length, for example a ruler. However, the ruler only has units of cm and mm. Therefore, teachers and students need innovative, creative and interesting learning media, one of which is developing Kilan Conversion Ruler media. The problems in this research are 1) How can the Kilan Conversion Ruler development media facilitate measuring and estimating length? 2) How is the suitability of the Kilan Conversion Ruler media able to facilitate measuring and estimating length? The aim of this research is to examine the feasibility of the Kilan Conversion Ruler media to facilitate measuring and estimating length and to examine the feasibility of the Kilan Conversion Ruler media to facilitate measuring and estimating length. The type of research used uses R&D (Research & Development) and the research and development stages use ADDIE. This research was conducted at SD Negeri Pagerharjo 01 Pati Regency. The results of the validity assessment of the Kilan Conversion Ruler media were declared valid. This is proven by the results of media expert validation of 89% and material validation of 86%. The percentage result obtained from the student figure the "agree" category. Meanwhile, the test results for one sample stated that the average tcount value was 13.5 > ttable 1.745. So there is a significant difference between student achievement in the control class and the experimental class. So that the results obtained, the Kilan Conversion Ruler media to facilitate measuring and estimating length for grade 2 elementary school students was developed effectively and is suitable for use in learning.